Digital Literacy: Effort to Increase Interest in Reading at SDN Nglumber II Kepohbaru Bojonegoro - Rohmatul Faizah (Nusantara Science and Technology Proceedings, 2022)
The goal of SDN Nglumber II Kepohbaru is to develop students' character by putting the school literacy motion policy into practice. The School Literacy Motion (GLS) is a result of the Minister of Education and Culture's Order No. 23 of 2015, which is focused on "The Development of Character." In order to promote critical thinking, problem-solving, scientific advancement, and the creation of a work, the literacy tradition relies on inquiry and the reading-writing approach. The purpose of this study is to clarify the school literacy motion policy at SDN Nglumber II Kepohbaru. This study employs a case study methodology as part of a qualitative descriptive investigation. Using interviews, discussion, and documentation as data collecting methods to confirm the reliability of the records, source triangulation was used. (1) At SDN Nglumber II Kepohbaru, programs like reading time, reading corners, storytelling, wall magazines, numeracy literacy, and comic creation support the GLS policy; (2) Supporting components for the GLS policy program's implementation at SDN Nglumber II Kepohbaru, include: the principal's dedication; parental participation; school community help; 15 minutes of time allocation for literacy; and varied media literacy. The inhibiting factors for GLS at SDN Nglumber II Kepohbaru consist of: insufficient books; insufficient library area; GLS bureaucratic structure that does not exist yet; and low reading awareness of students.